Mathematical simulation of the correlation between the frequency of road traffic accidents and driving experience - Miškinis, Paulius; Valuntaitė, Vaida (Transport, 2010)
Based on statistical analysis indicating the dependence of the number of road traffic accidents on driving experience, a mathematical model of such correlation is offered. The mathematical model has been tested generating a new approximation using the eigenfunctions of the introduced model applied to draw long‐term forecasts for the dependence of the number of potential road accidents on driving experience. Since we have more road traffic accidents per one hundred thousand inhabitants than other EU countries, comprehensive data analysis might also be useful for the EU community.First published online: 10 Feb 2011